2016
DOI: 10.1155/2016/1537276
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Nasopharyngeal Angiofibroma Presenting with Acute Airway Obstruction

Abstract: We describe a case of a 24-year-old male presenting urgently with a juvenile nasopharyngeal angiofibroma (JNA) with difficulty breathing, inability to swallow, and respiratory distress following throat swelling. The swelling was reduced with administration of dexamethasone and the JNA was surgically resected within 48 hours. This presentation was atypical given the acuity of presentation and the patient's older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Airway management is rarely a problem in JNA, even if the disease progresses. Wheat et al [3] reported a case of JNA causing acute airway obstruction in an adult male, but we could find no other reports.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Airway management is rarely a problem in JNA, even if the disease progresses. Wheat et al [3] reported a case of JNA causing acute airway obstruction in an adult male, but we could find no other reports.…”
Section: Discussionmentioning
confidence: 58%
“…The standard treatment of JNA is surgical resection after angiographic embolization. However, the anesthetic management is difficult due to the risk of massive bleeding because of the hypervascularity of JNA ; only one reported case has involved a difficult airway .…”
Section: Introductionmentioning
confidence: 99%
“…It is histologically benign, but aggressively invades local structures with various complications. 3,6 There is a case report of a late presentation of JNA with severe airway obstruction requiring tracheostomy. 7 We can conclude that our patient's OSA was caused by this space-occupying lesion, evidenced by complete resolution of OSA symptoms with CPAP and a postsurgical AHI of 0.5 events/h (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Efikasi masih terbatas pada pasien post pubertas, tidak efektif pada pasien pre pubertas karena kadar testosteron minimal atau bahkan tidak ada. 4,15 Embolisasi preoperatif sekarang rutin dilakukan dan bersamaan dengaan gelfoam atau partikel polyvinyl alcohol (PVA) 1-2 hari sebelum operasi. Hal ini dapat menurunkan kehilangan darah intraoperatif sampai 70% dan meningkatkan area pembedahan sehingga eksisi tumor komplit dapat dicapai.…”
Section: Pembedahan Dan Embolisasiunclassified